Public Debt Carrying Capacity and Debt Transmission Channels: The Nigerian Experience - Ebi, Bassey Okon; Imoke, Imoke Douglas (International Journal of Economics and Financial Issues, 2017)
Public debt is good but also harmful depending on the level of accumulation and its management. Different levels of public debt is said to have varied impact on growth and since a tolerable public debt level is necessary for economic growth, then, the rising public debt, low investment and non-inclusive economic growth in Nigeria is something to worry about. This study therefore, empirically investigates the debt growth relationship in Nigeria for the period 1970 -2014. Quadratic function was employed in modeling the various relationship of interest. Error Correction Mechanism (ECM) technique was applied to estimate the models. The results showed public debt to GDP ratio was positive while the squared of Public debt to GDP was negative and statistically significant at 5 percent level in the different equations. The result supported the presence of non-linearity as the positive coefficient of public debt at the lower level and negative coefficient at higher level demonstrates an inverted U-curve in the debt growth relationship. The study further indicated that the optimal debt carrying capacity of Nigeria is 29.7 percent debt GDP ratio. This implies that, the level of borrowing in Nigeria should not exceed this threshold otherwise it will exert a negative impact on the economy. The result also suggests that, investment, interest rates and private savings are channels through which public debt impact on economic growth in Nigeria. The paper recommended that due attention should be given to existing debt level before contracting new loans to avoid the economy being thrown into debt overhang. Borrowed funds should be channeled properly to investment in order to boost economic growth. Keywords: Public debt, Carrying capacity, Channels, Nigeria JEL Classifications: H63, O40